Islamic Radio In The Digital Age: Challenges And Opportunities For Survival - Ahmad Salman Farid; Musawer Hakimi (INJECT (Interdisciplinary Journal of Communication), 2025)
Islamic radio has historically served as a powerful medium for religious instruction, moral guidance, and community cohesion, particularly in regions with limited literacy or internet access. However, the rise of digital media has significantly altered consumption habits, especially among youth. This study employs a qualitative case study method, drawing on interviews, observations, surveys, and content analysis across several Islamic radio stations. Results indicate a steep decline in FM-based listenership, contrasted by rising engagement with Islamic digital media platforms. Stations that embraced digital innovation, mobile apps, live-streaming, AI-driven personalization, and collaborations with digital influencers demonstrated greater audience retention and reach. The paper argues that digital migration is essential, not optional, for the survival of Islamic radio. However, this transformation must be strategically managed to ensure theological authenticity, audience trust, and equitable digital access. The study provides actionable strategies for sustainable transition, while acknowledging limitations in sample diversity and calling for future research on comparative and longitudinal impacts.